Managing risk and decision making in times of economic distress - Grima, Simon; Özen, Ercan; Romānova, Inna (Emerald Publishing Limited, 2022)
Managing Risk and Decision Making in Times of Economic Distress adds much needed scholarly analysis of the fledgling decision/control approach, arguing the merits of its empirical content to shed light on the structure of capital contracts and rationale for diversity of objectives. Underpinning the book's central arguments are questions surrounding the identification and realisation of opportunities during periods of distress or disruption. Although such questions have been the focus of corporate finance, risk management, and financial management studies and literature, within the context of COVID-19 gaps remain unresolved. Continuity should be a proactive living plan to return to the norm we know, and continuity planning forms an integral part of a risk management strategy. With the future set to be shaped by these many disruptions and humanity's responses to it, critical insights are more important than ever, to ensure and determine progress towards the Sustainable Development Goals and recovering from these economic and social challenges. Contemporary Studies in Economic and Financial Analysis publishes a series of current and relevant themed volumes within the fields of economics and finance. Both disciplinary and interdisciplinary studies are welcome.
Keywords: Financial risk management.; Economic development.; Decision making -- Economic aspects.; Business & Economics -- Insurance / Risk Assessment & Management.; Economic growth.; elektronické knihy; electronic books